2007
DOI: 10.1080/07388550701775901
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Water on Enzyme Performance with an Emphasis on the Reactions in Supercritical Fluids

Abstract: Enzymes require a certain level of water in their structures in order to maintain their natural conformation, allowing them to deliver their full functionality. Furthermore, as a modifier of the solvent, up to a certain level, water can modify the solvent properties such as polarity/polarizability as well as the solubility of the reactants and the products. In addition, depending on the type of the reaction, water can be a substrate (e.g., in hydrolysis) or a product (e.g., in esterolysis) of the enzymatic rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(40 citation statements)
references
References 65 publications
1
36
0
2
Order By: Relevance
“…The reduction of enzyme activity after SC-CO 2 exposure has been related to several reasons. One of them is the water content needed to preserve the conformation of enzyme, and thus its optimal activity [24,43]. Therefore, the effect of the number of depressurization/pressurization cycles on the residual activity (%) and water content (%) of Lipozyme 435 treated with SC-CO 2 was evaluated.…”
Section: Reuse Of Lipozyme 435mentioning
confidence: 99%
“…The reduction of enzyme activity after SC-CO 2 exposure has been related to several reasons. One of them is the water content needed to preserve the conformation of enzyme, and thus its optimal activity [24,43]. Therefore, the effect of the number of depressurization/pressurization cycles on the residual activity (%) and water content (%) of Lipozyme 435 treated with SC-CO 2 was evaluated.…”
Section: Reuse Of Lipozyme 435mentioning
confidence: 99%
“…Several studies proved that a wide variety of organic solvents are able to denature enzymes [65][66][67][68][69][70][71] where the dehydration step required before dissolving an enzyme in an organic medium. The dehydration induces major perturbations of the secondary structure and gives some advantages such as the prevention of autolysis and an increase of the thermostability [65][66][67][68][69][70][71]. Dobson et al [58] considered that these effects are traced back to the fact that the presence of an organic solvent increases the interactions with the enzyme bound, the layer of water surrounding enzymes rather than with the enzyme itself.…”
Section: Organic Solvent Effectmentioning
confidence: 99%
“…Water activity (a w ) is indicative of water content around enzymes, and it is defined as the partial vapor pressure of water in a substance divided by the standard state partial vapor pressure of water. a w is an important consideration for enzyme activity in non-aqueous media because enzymes require a certain level of water in their structures (bound water) to maintain their natural conformation, allowing them to deliver their full functionality [19]. Bovara et al [3] reported that water activity ranging from <0.1 to 0.53 does not influence the enantioselectivity of enzymes in organic solvents using lipase PS and lipoprotein lipase as models.…”
Section: Effect Of Log P Value Of Organic Solventmentioning
confidence: 99%